2017
DOI: 10.5267/j.jpm.2017.5.002
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for crashing projects by considering time, cost, quality and risk

Abstract: Employers are looking for reducing execution time and maintaining the quality of the projects that are the main objective of the projects. In this article, we focus on crashing projects by considering different factors such as cost, time, quality and risk. For the proposed integer linear model, cost of conformance and cost of non-conformance are considered as parts of the costs of quality of deliverables in projects. The cost of conformance consists of the costs of training the project team, inspection and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Nowadays project management has many applications in different fields such as construction, healthcare and so on. Project is a temporary effort with a specific start and end point [1]. A project can be a unique service or product.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays project management has many applications in different fields such as construction, healthcare and so on. Project is a temporary effort with a specific start and end point [1]. A project can be a unique service or product.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, project management has been addressed from the perspective of sustainability. Kivilä et al [23] identified the control practices used for sustainable project management, and a case study was conducted on a large infrastructure project. By analyzing a survey completed by project managers, Martens and Carvalho [24] suggested four factors that affected project management: economic and competitive advantage, sustainable innovation business model, environmental policies and resource-saving, and stakeholder management.…”
Section: Project Managementmentioning
confidence: 99%
“…However, resources are limited and resource-constrained project scheduling is itself a noted problem in project management literature (Kasravi et al , 2018; Afruzi et al , 2014). In light of the PMBOK® Guide , Mahmoudi and Feylizadeh (2017) regarded crashing to be “the key technique for reducing project duration.” When crashing techniques are deployed, the project scope is considered to be fixed and an attempt is made to balance the cost and time within that scope (Mahmoudi and Feylizadeh, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%